Development of Thai Spondee Words for SRT Measurement in Children - Dermtoranin, Kanang; Lertsukprasert, Krisna; Lao, Mena; Maroonroge, Sumalai (Biomedical Sciences and Clinical Medicine, 2022)
Abstract Objective: The purpose of this study was to develop a standardized Thai speech material to be used in the measurement of speech recognition threshold (SRT) in children. Methods: The Thai speech material have been developed according to three essential criteria: word familiarity to the children, phonetic dissimilarity, and homogeneity with respect to basic audibility. The disyllabic words selected from a Thai fundamental word list, used in teaching Thai language at the first level, were analyzed to measure the intensity of each syllable. These spondee words were then assessed for familiarity. As a result, a total of 60 spondee words have been selected to evaluate the threshold of recognition of each word by 30 normal-hearing children. Results: From the 60 spondee words, there were 25 spondee words, with relatively steep and homogeneous psychometric function slopes, selected to be included in a list of Thai speech material for children. The psychometric functions slopes at the 50% threshold of the final 25 spondee words, were found to have a mean of 10.76 %/dB. Conclusions: The Thai speech material for children were developed according to the speech material criteria. Hence, this list can be used to evaluate the SRT of normal hearing children.